Relationship Between Students’ Self Confidence Attitude and Assertive Attitude Among Student of Grade XI at SMAN 2 Gorontalo - Usman, Irvan; Djibran, Moh Rizki; Ahsan, Sukria (International Journal of Applied Guidance and Counseling, 2020)
School is considered a place where the students are familiar with new attitudes in life. It is expected that they can recognize a new positive attitude, such as an assertive attitude. The aim of the research is investigating students’ self-confidence behavior with assertive at grade XI of SMAN 2 Gorontalo. The population of this research was 310 students, while its samples were 31 people determined by random sampling. Data are collected through a scale of self-confidence and an assertive attitude. The data were analyzed with regression analysis. Research findings showed that there is a significant correlation between students’ self-confidence and assertive attitude. Variation of students’ self-confidence is 44,19% for assertive attitude, while the remaining 55,81% is followed by other behaviors and attitudes that are not revealed in this research. This study concludes that there is a correlation between self-confidence and assertive behavior on grade XI students of SMA N 2 Gorontalo.